Interstitial lung disease after receiving the mRNA-based COVID-19 vaccine tozinameran. (2022) - Oda, Naohiro; Mitani, Reo; Takata, Ichiro; Kataoka, Mikio
Abstract: Tozinameran, a messenger ribonucleic acid (mRNA)-based coronavirus disease 19 (COVID-19) vaccine, has a favorable safety profile and is highly efficacious in preventing COVID-19. Adverse reactions such as pain at the vaccination site, fever, malaise, headache, rash, and anaphylaxis have been commonly reported for mRNA-based COVID-19 vaccines. We report a case involving a 71-year-old Japanese woman who developed interstitial lung disease (ILD) after receiving an mRNA-based COVID-19 vaccine. We also review case reports of COVID-19 mRNA vaccine-associated ILD. Dyspnea or hypoxia that develops within 1–3 days after COVID-19 mRNA vaccination should be differentiated from ILD. Further studies to elucidate mechanisms and risk factors of rare adverse reactions such as ILD are warranted.